’N ONWAARSKYNLIKE VOORSTEL VIR ’N ONGELOOFLIKE SPEL - Holloway, J.E. (Scientia Militaria - South African Journal of Military Studies, 2012)
A parallel is drawn between the game of chess and the ’game’ of war and the use of credit cards in the civilian world and that of credits obtained or lost in the world of the soldier. Certain similarities are pointed out as well as a number of differences. Suggestions are put forth to improve the players’ game and whereas (as the author points out) his suggestions are rather unlikely as far as the ’game’ of war and soldiering are concerned, it is nevertheless unbelievably realistic and so gripping that you find yourself wondering: is it really so far-fetched an idea?